Partner Choices in Long Established Migrant Communities in Belgium - Emilien Dupont; Amelie Van Pottelberge; Bart Van de Putte; John Lievens; Frank Caestecker (Historical Life Course Studies, 2017)
This paper aims to shed light on the partner choices of Moroccan, Turkish, Congolese, and Algerian migrants in Belgium. Three partner choices are distinguished: marrying a partner from the country of origin (partner migration), marrying a local co-ethnic partner, and establishing a mixed marriage. We focused on the role of migration history and transnational links, culture (religion, language), skin colour and structural characteristics of the district migrants live in (mainly community size) to gain further insight into the partner choices of migrants in Belgium. Our data comprise an extraction of the Belgian national register (2001-2008) and focus on first marriages among first, 1.5, and second generation migrants of Moroccan, Turkish, Algerian, and Congolese origin (N=52,142). We apply a multinomial logistic multilevel design to simultaneously incorporate individual and contextual effects at the district level. The main conclusion from this paper is that the partner selection pattern in early 21st century Belgian society still bears the traces of the starting conditions that migrant groups experienced when they first entered the country. While this continuity is important to understand the situation citizens with a migrant origin have to deal with today, it does not make change impossible. In fact, for the Turkish and Moroccan group, research recently showed a quite strong decline in transnational marriages and a modest increase in mixed marriages. These are indications that after 50 years of migration a transition towards full inclusion in Belgian society is not beyond reach. The conditions analysed in this paper, namely the strength of transnational networks, the cultural boundaries and the ethnic community size, may help to understand why this inclusion takes such a long period of time.